Time in the Contemporary World: school time and curricular justice - Branca Jurema Ponce (Universidade Federal do Rio Grande do Sul, 2016)
School education constitutes a locus of power struggles, expressed most emphatically by the battle to define curricula, which are contaminated by the pace of the global economy and by the search for results in national and international educational rankings. In consequence, the school is facing a fast and immediatist routine that favors a time emptied of reflection. In this context, an existing problem was significantly deepened: the 'school time', object of this paper, which proposes the curriculum as a social instrument of collective responsibility, aiming at social justice. The goal is to characterize the time in which education is built as one of the most important aspects of the school curriculum.